Respuestas

  • Usuario de Brainly
2014-02-26T02:48:41+01:00
Solución:
=> 5(P - 7)^2 - (3P - 4) = 3P
=> (5) (P^2 - (2)(P)(7) + (7)^2) - 3P + 4 = 3P
¡> (5)(P^2 - 14P + 49) - 3P + 4 = 3P
=> 5P^2 - 70P + 245 - 3P + 4 = 3P
=> 5P^2 - 73P + 249 = 3P
=> 5P^2 - 73P + 249 - 3P = 0
=> 5P^2 - 76P + 249 = 0
Resolviendo esta ecuación cuadrática por fórmula, tenemos:
Donde a: 5 , b: -76 , c: 249
.............................________________
=> P = [ - (-76) +- V((-76)^2 - (4)(5)(249)) ] / (2 x 5)
........................___________
=> P = [ 76 +- V(5776 - 4980) ] / 10
........................____
=> P = [ 76 +- V(796) ] / 10
.........................______
=> P = [ 76 +- 2V(199) ] / 10
...............................____.........................____
=> P(1) = [ 2 ( 38 + V(199) ] / 10 = [ 38 + V(199) ] / 5 => Respuesta
........................._____
=> P(2) = [ 38 - V(199) ] / 5 => Respuesta.

SUERTE.